2019
DOI: 10.1002/pon.5096
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic associations between perceived social support and cancer patient and caregiver health: An actor‐partner interdependence modeling approach

Abstract: Objective: Social support may have a positive impact on health outcomes for patients and caregivers, but the extent to which social support and health outcomes are interrelated for both is unknown. We examine the dyadic interrelationships between social support and health among cancer patients and their caregivers. Methods: Lung and colorectal cancer (CRC) patient and caregiver dyadic data were obtained from the Cancer Care Outcomes Research and Surveillance Consortium. Patients and caregivers self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 32 publications
(57 reference statements)
7
39
0
3
Order By: Relevance
“…Finally, and contrary to what was expected, no statistically significant associations between social support and pain interference with daily activities were found. Although some studies have shown that social support is an important factor in relation to chronic pain and disability (Matos, Bernardes, & Goubert, ; Kelley, Kent, Litzelman, Mollica, & Rowland, ), others have found, in line with the present study, no significant relationships between these variables (Tan & Wang, ; Uchino, Bowen, Carlisle, & Birmingham, ). One explanation for the inconsistency of these findings could be related to the characteristics of the samples included in the studies, both in terms of the pain problem and the perceived need for social support.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, and contrary to what was expected, no statistically significant associations between social support and pain interference with daily activities were found. Although some studies have shown that social support is an important factor in relation to chronic pain and disability (Matos, Bernardes, & Goubert, ; Kelley, Kent, Litzelman, Mollica, & Rowland, ), others have found, in line with the present study, no significant relationships between these variables (Tan & Wang, ; Uchino, Bowen, Carlisle, & Birmingham, ). One explanation for the inconsistency of these findings could be related to the characteristics of the samples included in the studies, both in terms of the pain problem and the perceived need for social support.…”
Section: Discussionsupporting
confidence: 80%
“… 39 The relationship between lung cancer and smoking, accented by years of anti-tobacco campaigns, has strengthened the belief that lung cancer patients are in some way responsible for their diagnosis and this leads to an internalisation of blame. 18 Johnson et al claimed that stigma may be important in terms of QoL for lung cancer patients and may independently influence social support and physical symptoms. 39 Chambers et al also noted that patients who feel this stigma face shame, fear and rejection, and have more limited social networks, all of which lead to diminished QoL and lower psychological welfare.…”
Section: Resultsmentioning
confidence: 99%
“…Patients and caregivers shared dimensions of time and adapted their daily routines to accommodate one another's health status (Nimmon). Also, actor and partner effects differed based on specific disease (Kelley et al, 2019). Latina/o caregivers have experienced higher reports of depression and caregiver burden compared to non-Latina/o whites in previous research (Linton & Kim, 2018;Arévalo-Flechas., Acton, Escamilla, Bonner, & Lewis, 2014).…”
mentioning
confidence: 83%
“…The interdependence between patients and caregivers has been studied most commonly among those experiencing cancer and heart disease (Buck, Mogle, Riegel, McMillan, & Bakitas , 2015;Ellis et al, 2017;Ivziku, Clari, Piredda, De Marinis, & Matarese, 2019;Kelley, Kent, Litzelman, Mollica, & Rowland, 2019;Kershaw et al, 2015, Lo et al, 2013Nimmon, Bates, Kimel, & Lingard, 2018;Shaffer, Kim, & Carver, 2016;Vellone et al, 2014). Interdependence is defined as "when the emotion, cognition or behavior of one partner in the relationship affects that of the other partner" (Jacobs, Clari, Piredda, De Marinis, & Matarese, 2017, p. 3).…”
mentioning
confidence: 99%